Entrepreneurial Behavior of Skilled Youths of Banda District of Bundelkhand Region, Uttar Pradesh - Singh, Saurabh; Gupta, B. K.; Mishra, B.P.; Shukla, Gaurav; Raghubanshi, Saurabh S.; Kalia, Abhishek; Kumar, Alok (Indian Journal of Extension Education, 2021)
India being predominantly agriculture and agripreneurs play vital and important role in the agricultural value chain. In today’s changing scenario, skills in entrepreneurship development have become important and Skill Development of Rural Youth is a flagship scheme of the Government of India. The study was conducted in Banda district of Bundelkhand region of Uttar Pradesh to study the entrepreneurial behaviour of youths and its impact on socio-economic status of youths. Total 90 respondents were selected through proportionate random sampling from three youth training centers of Banda district. The data were collected with the help of pre-structured schedule and entrepreneurial behaviour of youths was assessed by seven components of entrepreneurial behaviour. It was found that the majority (66.67%) of respondents had medium level of entrepreneurial behaviour. Further, the socio-economic profile attributes like education, land holding, material possession, occupation, annual income and sources of information utilization were positively and significantly correlated with entrepreneurial behaviour of youths.